Synthesis of the silver nanoparticles stabilized by bovine serumalbumin and investigation of their electrochemical properties; Instrumental Methods of Analysis: Modern Trends and Applications (IMA-2017) - Khristunova E. Ekaterina; Korotkova E. I. Elena Ivanovna; Barek J. Irzhi; Kratokhvil B. Bokhumil (2017, 2017)
Title screen